Fiqh Siyasah and the State: Mapping Paradigms of Religion-State Relations in Modern Islamic Thought - Munir, Misbahul (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2023)
This study aims to examine the role of fiqh siyasah (Islamic political jurisprudence) in state governance and to explore the evolving relationship between religion and the state. As political dynamics shift, the relevance of fikih siyasah in modern governance remains a significant issue in Islamic scholarship. Employing a qualitative descriptive-analytical method, this research is grounded in normative theological approaches that refer to fundamental Islamic values. Data were collected and analyzed through a literature-based study, focusing on classical and contemporary Islamic legal texts. The findings reveal two main points: first, fikih siyasah functions as an Islamic legal instrument that guides governmental authority in implementing Islamic laws for societal welfare. Second, the relationship between religion and state is understood through three paradigms: secularistic (separating religion from state), formalistic (asserting Islam as a comprehensive system governing all aspects of life), and substantialistic (emphasizing moral and ethical values without asserting total political control). This study offers originality by mapping these paradigms within the framework of contemporary Islamic political thought, highlighting their coexistence and tension. The implications of this research suggest a need for contextual and balanced interpretations of fikih siyasah to support harmonious relations between Islamic principles and state institutions in pluralistic societies.